The role of people and organisations in learning technology practice - Frances Bell (Association for Learning Technology, 2011)
This issue of Research in Learning Technology reflects the importance of people and organisations in the effective application of learning technology. Our journal aims (amongst other goals) to spread good practice in the use of learning technology, and the papers in this issue can help to achieve this aim. Creating an issue is as much about happenstance as planning but it is always interesting to see what the assembled papers have in common. In this collection of papers, there is a strong practice theme emerging.